Galectin-3 and blood group: binding properties, effects on plasma levels, and consequences for prognostic performance - Pozder, Carolin; Screever, Elles M.; van der Velde, A. Rogier; Silljé, Herman H.; Suwijn, Janne; de Rond, Saskia; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Schuringa, Jan Jacob; Gilst, Wiekert H. van; Meijers, Wouter C.; März, Winfried; et al. (International journal of molecular sciences, 2023)
Previous studies have reported an association between ABO type blood group and cardiovascular (CV) events and outcomes. The precise mechanisms underpinning this striking observation remain unknown, although differences in von Willebrand factor (VWF) plasma levels have been proposed as an explanation. Recently, galectin-3 was identified as an endogenous ligand of VWF and red blood cells (RBCs) and, therefore, we aimed to explore the role of galectin-3 in different blood groups. Two in vitro assays were used to assess the binding capacity of galectin-3 to RBCs and VWF in different blood groups. Additionally, plasma levels of galectin-3 were measured in different blood groups in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study (2571 patients hospitalized for coronary angiography) and validated in a community-based cohort of the Prevention of Renal and Vascular End-stage Disease (PREVEND) study (3552 participants). To determine the prognostic value of galectin-3 in different blood groups, logistic regression and cox regression models were used with all-cause mortality as the primary outcome. First, we demonstrated that galectin-3 has a higher binding capacity for RBCs and VWF in non-O blood groups, compared to blood group O. Additionally, LURIC patients with non-O blood groups had substantially lower plasma levels of galectin-3 (15.0, 14.9, and 14.0 μg/L in blood groups A, B, and AB, respectively, compared to 17.1 μg/L in blood group O, p < 0.0001). Finally, the independent prognostic value of galectin-3 for all-cause mortality showed a non-significant trend towards higher mortality in non-O blood groups. Although plasma galectin-3 levels are lower in non-O blood groups, the prognostic value of galectin-3 is also present in subjects with a non-O blood group. We conclude that physical interaction between galectin-3 and blood group epitopes may modulate galectin-3, which may affect its performance as a biomarker and its biological activity.